CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND BATAK TOBA LANGUAGE IN QUESTION WORD - Pasaribu, Septiana Hirawati; Tampubolon, Apnes; Sidauruk, Anni; Napitupulu, Selviana (Transpublika Publisher, 2022)
This research intends to establish the similarities and differences in question words when using English and the Toba Batak language. It used a qualitative descriptive research design. Documentation techniques were used to collect the data. The researcher used descriptive analysis to analyze the data. The question words in English consist of 9 question words, which are as follows: